Challenges and Strategies of Transition from Graduation to Work in the Post-2020 Asia Pacific and Beyond: A Comparative Analysis of Nine Countries - Dhakal, Subas P.; Nankervis, A.; Burgess, K.; Verma, P. (Springer, 2019)
The successful transition of higher education (HE) and vocational education and training (VET) graduates from education to work is central to achieving sustainable human development across the Asia Pacific and beyond. For instance, the composite Human Development Index (HDI) developed by the United Nations indicates the wide ranging socio-economic ranking of the nine country cases represented in this book. And yet, many of the country cases represented in this book are facing various policy challenges linked to upskilling and overcoming skill shortages. It is in this context that the chapter aims to investigate: ‘how different countries operating in different socio-economic circumstances are trying to facilitate the transition from graduation to work?’ The chapter adopts a Leximancer-based innovative content analysis technique to explore the question. In addition, the chapter also provides a comparative synopsis of innovative graduate work-readiness initiatives across the included countries.